2021
DOI: 10.1007/s00453-020-00791-7
|View full text |Cite
|
Sign up to set email alerts
|

Popular Matchings in Complete Graphs

Abstract: Our input is a complete graph G on n vertices where each vertex has a strict ranking of all other vertices in G. The goal is to construct a matching in G that is popular. A matching M is popular if M does not lose a head-to-head election against any matching $$M'$$ M ′ : here each vertex casts a vote for the matching in $$\{M,M'\}$$ { M , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For graphs with an even n, our algorithm is only able to decide whether a non-perfect popular matching exists. This is not surprising, because deciding whether a (perfect) popular matching exists in a complete graph with an even n is NP-complete [7], while our algorithm runs in polynomial time if |U | is small and the minimum degree in the graph is large.…”
Section: Correctness and Running Timementioning
confidence: 86%
See 3 more Smart Citations
“…For graphs with an even n, our algorithm is only able to decide whether a non-perfect popular matching exists. This is not surprising, because deciding whether a (perfect) popular matching exists in a complete graph with an even n is NP-complete [7], while our algorithm runs in polynomial time if |U | is small and the minimum degree in the graph is large.…”
Section: Correctness and Running Timementioning
confidence: 86%
“…Only recently Faenza et al [12] and Gupta et al [15] resolved the long-standing [2,5,18,20,29] open question on the complexity of deciding whether a popular matching exists in a popular roommates instance and showed that the problem is NP-complete. This hardness result remains valid even if the preference lists are complete [7]. However, this hardness result is only valid for complete graphs with an even number of vertices.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, Faenza et al [6] and Gupta et al [10] independently proved that this problem is still NPhard for rp even when people's preference lists are strict. Cseh and Kavitha [4] showed that, in a complete graph rp instance where each person's preference list is strict and contains all other people, the problem of determining whether a popular matching exists can be solved in polynomial time for an odd n but is NP-hard for an even n.…”
Section: Popular Matchingsmentioning
confidence: 99%